Nourishing Smiles: The Impact of Nutrition on Children’s Dental Health (Academia Journal of Medicine, 2025)
This article explores the relationship between nutrition and dental health in children. Good nutrition is essential for overall health and well-being, yet its impact on dental health is often overlooked. Dental cavities and other oral health issues are largely preventable through proper dietary habits. This research examines essential nutrients, dietary recommendations, and the effects of sugar and acidic foods on children’s oral health. Additionally, it discusses the role of parents, schools, and public health policies in promoting better nutrition and oral hygiene practices.
Keywords: oral health; nutrition; food-based dietary guidelines; pre-school children